The introduction of self-driving / full-automation trucks: Will we live among these modern dinosaurs? - Arne Schulke; Mai Vi Nguyen (IU Internationale Hochschule, 2023)
Road transportation accounts for most of the freight transportation in the EU, with trucks responsible for 71.3 percent of all inland EU freight movements. The trucking industry in the EU is facing several challenges and Selfdriving Trucks (SDTs) seem to be a promising solution to its problems. This study explores the current state of selfdriving technologies and the benefits and drawbacks associated with SDTs. Furthermore, the study tries to examine how the European public perceives the use of SDTs. This study utilized a mixed method, integrating qualitative and quantitative: Qualitative data were collected by means of a thorough literature review. The public's perception was assessed through a survey, from which quantitative data were extracted. There were 256 participants who answered the survey. Key findings are that the EU public is aware of Self-driving Vehicles (SDVs) but less aware of SDTs. Most people perceive self-driving technology positively and believe that the implementation of SDTs will have profound effects on both the logistics as well as the trucking industry in particular. Even though most participants perceived SDVs to drive better than humans, thus increasing road safety, 67.2 percent did not want to share the road with them. This raises severe challenges for policy makers towards public acceptance of their wide-scale introduction.
Keywords: M10; M19; R41; 650; automation; automated driving; self-driving truck; public perception; freight transport